Pengaruh Solvabilitas, Reputasi Auditor dan Kepemilikan Publik terhadap Audit Delay - Febrina Ayu Finsensia; Agus Munandar (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to examine the effect of solvency, auditor reputation and public ownership on audit delay in trading, service and investment companies listed on the Indonesia Stock Exchange in 2017-2019. This study uses secondary data that takes financial statement data from the IDX. This sample amounts to 74 ownership and uses multiple linear regression.The results of this study that the solvency variable does not affect the audit delay, the auditor reputation variable does not affect the audit delay and the variable public ownership affects the audit delay.